Microbial profile in bile from pancreatic and extra-pancreatic biliary tract cancer. - Paola Di Carlo; Nicola Serra; Teresa Maria Assunta Fasciana; Anna Giammanco; Francesco D'Arpa; Teresa Rea; Maria Santa Napolitano; Alessandro Lucchesi; Antonio Cascio; Consolato Maria Sergi (PLoS ONE, 2024)
Background Dysbiotic biliary bacterial profile is reported in cancer patients and is associated with survival and comorbidities, raising the question of its effect on the influence of anticancer drugs and, recently, the suggestion of perichemotherapy antibiotics in pancreatic cancer patients colonized by the Escherichia coli and Klebsiella pneumoniae. Objective In this study, we investigated the microbial communities that colonize tumours and which bacteria could aid in diagnosing pancreatic and biliary cancer and managing bile-colonized patients. Methods A retrospective study on positive bile cultures of 145 Italian patients who underwent cholangiopancreatography with PC and EPC cancer hospitalized from January 2006 to December 2020 in a QA-certified academic surgical unit were investigated for aerobic/facultative-anaerobic bacteria and fungal organisms. Results We found that among Gram-negative bacteria, Escherichia coli and Pseudomonas spp were the most frequent in the EPC group, while Escherichia coli, Klebsiella spp, and Pseudomonas spp were the most frequent in the PC group. Enterococcus spp was the most frequent Gram-positive bacteria in both groups. Comparing the EPC and PC, we found a significant presence of patients with greater age in the PC compared to the EPC group. Regarding Candida spp, we found no significant but greater rate in the PC group compared to the EPC group (11.7% vs 1.96%). We found that Alcaligenes faecalis was the most frequent bacteria in EPC than the PC group, among Gram-negative bacterial species. Conclusions Age differences in gut microbiota composition may affect biliary habitats in our cancer population, especially in patients with pancreatic cancer. Alcaligenes faecalis isolated in the culture of bile samples could represent potential microbial markers for a restricted follow-up to early diagnosis of extra-pancreatic cancer. Finally, the prevalence of Candida spp in pancreatic cancer seems to trigger new aspects about debate about the role of fungal microbiota into their relationship with pancreatic cancer.